2017
DOI: 10.3390/w9120925
|View full text |Cite
|
Sign up to set email alerts
|

Urban Flood Simulation Using Synthetic Storm Drain Networks

Abstract: Recent developments in urban drainage modelling allow for a more realistic coupling of the two-dimensional (2D) surface and one-dimensional (1D) sub-surface drainage domain exchanging water through storm drain inlets instead of a sub-catchment approach based on manholes. Experience has shown, however, that comprehensive records of storm drain inlet locations are often missing or incomplete, preventing users accessing the full benefit of these modelling capabilities. Therefore, this study developed a GIS routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Because of their superior performance, the upwind flux solver has been preferred over general hyperbolic conservation systems such as compressible flow, hydrodynamics systems, and shallow water systems, etc. [3,13,16,[19][20][21]. However, for the Preissmann slot model, the monotonicity is not guaranteed by the widely used Riemann flux solvers because of the highly irregular shapes of pipes connected to the hypothetical slot, as presented in numerous previous works [5,10,22], whereas it is preserved for a regular-shaped flow domain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of their superior performance, the upwind flux solver has been preferred over general hyperbolic conservation systems such as compressible flow, hydrodynamics systems, and shallow water systems, etc. [3,13,16,[19][20][21]. However, for the Preissmann slot model, the monotonicity is not guaranteed by the widely used Riemann flux solvers because of the highly irregular shapes of pipes connected to the hypothetical slot, as presented in numerous previous works [5,10,22], whereas it is preserved for a regular-shaped flow domain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [1,2] has shown that a compressible one-dimensional fluid equation with a linearized pressure law is an attractive alternative for modeling of transient mixed flows in pipe; however, a compressible fluid system is more complex to solve than a one-dimensional shallow water system usually used to represent open channel flows. The Preissmann slot model can avoid this difficulty and has been widely used to solve multiple flow conditions in sewer systems [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their solution combines rainwater management with computer-aided design (CAD) software, and offers a visualisation of the landscape and buildings, runoff flow paths, and directions analysis, as well as a friendly interface developed with architects and landscape designers in mind. The newly-developed City Catchment Analysis Tool (CityCAT) can be applied for designing better urban drainage and locating storm drain inlets [43].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [8] developed a planning support model that combines rainwater management with Computer-Aided Design (CAD) software. Finally, the City Catchment Analysis Tool (CityCAT) by Bertsch et al [64] can be applied for better urban drainage designing and locating storm drain inlets. Overall, integrated systems combine pluvial flood risk mapping with water management tasks, as well as the economic effectiveness of flood control and adaptation measures [14].…”
Section: Introductionmentioning
confidence: 99%